The specific mitochondrial unfolded protein response in fast- and slow-twitch muscles of high-fat diet-induced insulin-resistant rats - Li, Can; Li, Nan; Zhang, Ziyi; Song, Yu; Li, Jialin; Wang, Zhe; Bo, Hai; Zhang, Yong (Frontiers in Endocrinology, 2023)
Skeletal muscle insulin resistance (IR) plays an important role in the pathogenesis of type 2 diabetes mellitus. Skeletal muscle is a heterogeneous tissue composed of different muscle fiber types that contribute distinctly to IR development. Glucose transportation shows more protection in slow-twitch muscles than in fast-twitch muscles during IR development, while the mechanisms involved remain unclear. Therefore, we investigated the role of the mitochondrial unfolded protein response (UPRmt) in the distinct resistance of two types of muscle in IR. Male Wistar rats were divided into high-fat diet (HFD) feeding and control groups. We measured glucose transport, mitochondrial respiration, UPRmt and histone methylation modification of UPRmt-related proteins to examine the UPRmt in slow fiber-enriched soleus (Sol) and fast fiber-enriched tibialis anterior (TA) under HFD conditions. Our results indicate that 18 weeks of HFD can cause systemic IR, while the disturbance of Glut4-dependent glucose transport only occurred in fast muscle. The expression levels of UPRmt markers, including ATF5, HSP60 and ClpP, and the UPRmt-related mitokine MOTS-c were significantly higher in slow muscle than in fast muscle under HFD conditions. Mitochondrial respiratory function is maintained only in slow muscle. Additionally, in the Sol, histone methylation at the ATF5 promoter region was significantly higher than that in the TA after HFD feeding. In conclusion, glucose transport in slow muscle is more protected than that in fast muscle after HFD intervention. Specific activation of the UPRmt in slow muscle, accompanied by higher mitochondrial respiratory function and MOTS-c expression, may explain the results. Notably, the different histone modifications of UPRmt regulators may underlie the specific activation of the UPRmt in different muscle types.